Strategy and Process of Human Development Infrastructure Planning in the Education Sector at the Regional Development Planning Agency of Garut District - Nafla Hasna Sania; Amalia Nur Rizki; Renaldy Aji Maulana; Ine Mariane (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose. This study aims to analyze the strategy and process of prioritizing human development infrastructure planning in the education sector at the Regional Development Planning Agency (BAPPEDA) of Garut Regency using Henry Mintzberg’s 5P strategy framework. Materials and methods. This research employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with planning actors involved in the formulation of the 2025 Regional Government Work Plan (RKPD), non-participant observation of planning forums, and document analysis of planning and regulatory documents. Data were analyzed interpretatively to capture meanings, patterns, and strategic practices in the planning process. Results. The findings reveal an imbalance in the application of strategic dimensions. Formal planning (plan) and repetitive administrative practices (pattern) dominate the planning process, while institutional positioning (position) and shared strategic perspectives (perspective) remain relatively weak. Tactical maneuvers (ploy) function as short-term adaptive strategies to address fiscal constraints and intersectoral competition but have not succeeded in driving substantive transformation in education infrastructure planning. Conclusions. This study concludes that the effectiveness of education infrastructure planning at the regional level is determined not merely by procedural completeness, but by the balance and integration of strategic dimensions. The findings contribute theoretically by demonstrating that strategic imbalance in public sector organizations results in administratively robust yet strategically fragile planning, limiting its capacity to support sustainable human development. Keywords: Strategic Planning; Education Infrastructure; Human Development; Public Sector Strategy; BAPPEDA